Effects of alpelisib treatment on murine Pten-deficient lipomas - Lea M. Merz; Karsten Winter; Sandy Richter; Sonja Kallendrusch; Andreas Horn; Sonja Grunewald; Nora Klöting; Kerstin Krause; Wieland Kiess; Diana Le Duc; Antje Garten (Adipocyte)
Phosphatase and tensin homolog (PTEN) hamartoma tumour syndrome (PHTS) is a rare disorder caused by germline mutations in the tumour suppressor gene PTEN, a key negative regulator of phosphatidylinositol 3-kinase (PI3K)/AKT signalling. Children with PHTS often develop lipomas, for which only surgical resection is available as treatment. We investigated the effects of the selective PI3K-inhibitor alpelisib on Pten-deficient lipomas. After incubation with alpelisib or the non-selective PI3K inhibitor wortmannin, we analysed histology, gene expression, and Pi3k pathway in lipoma and control epididymal adipose tissue (epiWAT). Alpelisib increased adipocyte area in lipomas compared to epiWAT. Baseline gene expression showed higher levels of markers for proliferation (Pcna), fibrosis (Tgfb1), and adipogenesis (Pparg) in lipomas, while hormone-sensitive lipase expression was lower than in epiWAT. Following alpelisib incubation, target genes of Pi3k signalling and extracellular matrix factors were reduced. We confirmed Pi3k inhibition through detecting decreased Akt levels compared to control treatment. Human lipoma samples treated with alpelisib showed variable lipolysis responses, suggesting variability in therapeutic outcomes. We established an ex vivo model to study alpelisib effects on Pten-deficient lipomas. These results underscore the therapeutic potential of targeted PI3K inhibition in the treatment of PHTS-associated lipomas, particularly in cases that are inoperable.